Experimental and theoretical investigations on the high-electron donor character of pyrido-annelated N-heterocyclic carbenes - Nonnenmacher, Michael; Buck, Dominik; Kunz, Doris (Beilstein journal of organic chemistry, 2016)
Beilstein Journal of Organic Chemistry
Gesehen am 05.11.2020